Sulphur dioxide sheet and cold storage synergy for post-harvest management of Thompson seedless grapes (Vitis vinifera) - Komal Mahajan; Mehul Chudasama (Journal of Horticulture and Postharvest Research, 2024)
Purpose: This study examined the influence of various storage conditions on Thompson seedless (Vitis vinifera) grapes quality. Research method: Grapes were stored under four conditions: control (room temperature i.e., 20-22°C, no SO2), T1 with SO2 sheets at room temperature i.e., 20-22°C, T2 with SO2 sheets in cold storage at 1°C and T3 without SO2 sheets in cold storage at 1°C. Changes in acidity, total soluble solids (TSS), total anthocyanin content, total phenols, sugars (glucose and fructose), trans-resveratrol, decay %, weight loss % and antioxidant activity were monitored over 60 days. Findings: The findings revealed a synergistic effect between SO2 and cold storage. Grapes stored with both SO2 sheets and cold storage (T1) exhibited the slowest decline in anthocyanin, phenols and antioxidant activity of 211.06 mg/L, 2102.39 mg/L and 7.19 mM DPPH, respectively after 60 days. T1 grapes found to have slower reduction in sugars and trans-resveratrol concentration i.e., 15.47 to 15.37 g/100mL and 695 to 516 µg/g, respectively compared to control samples 15.47 to 14.81 g/100mL and 695 to 500 µg/g, respectively. Research limitations: The study focused solely on storage conditions of Thompson seedless variety grapes, limiting the generalizability of the findings to different grape varieties and maturity levels. Originality/value: These results highlighted the importance of proper storage techniques, particularly the combined use of SO2 and cold storage, for maintaining grape quality and extending shelf life.